Analisis dan Perancangan Sistem Informasi Administrasi RT/RW Berbasis Website Menggunakan Standar ISO/IEC 25010 pada PT Teknologi Informatika Solusindo - Muhammad Naufal Skha Yusfa; Almy Rizki Akbar; Chairul Anwar (Journal of Information Systems and Business Technology, 2026)
The development of information technology has encouraged digital transformation in various administrative sectors, including neighborhood administration services at the RT/RW level. Administrative processes that are still conducted manually often lead to data recording errors, delays in information delivery, difficulties in document archiving, and reduced service efficiency. This study aims to analyze and design a web-based RT/RW administrative information system at PT Teknologi Informatika Solusindo using the Prototype development method and the ISO/IEC 25010 standard as a system quality evaluation framework. Data collection techniques employed in this research include observation, interviews, documentation, and literature study. The system development process consists of communication, quick planning, modeling, prototype construction, and user evaluation stages. The designed system provides features for resident data management, correspondence administration, complaint services, and information dissemination. System testing refers to eight ISO/IEC 25010 quality aspects, including Functional Suitability, Performance Efficiency, Compatibility, Usability, Reliability, Security, Maintainability, and Portability. The results indicate that the developed system can improve administrative effectiveness, facilitate data management, and support more structured and transparent administrative services.